Nozzle type and adjuvant selection influence on nicosulfuron efficacy on some common weeds in maize (Zea mays L.) - Jovanović, Darko (Acta herbologica, 2024)
The field experiment was conducted during 2021 and 2022 at the Maize Research Institute Zemun Polje, Zemun Polje in Serbia. The goal of this study was to evaluate the influence of adjuvants and nozzle types on the efficacy of two herbicides based on the same active ingredient - nicosulfuron. The study was arranged as a split-block design in four replication with 12 treatments plus weed-free as well as weedy season long treatments. 21 day after treatment (DAT) weeds were sampled and both fresh as well as dry biomas were measured (only dry biomass showed). Visual estimation of efficacy was assessed 7, 14 and 21 DAT. Among all treatments no differences between herbicides were observed. In addition, treatments with AMS caused a rapid decrease of efficacy compared to treatments with non-ionic surfactant (NIS) adjuvant where the efficacy was increased and where it lead to faster weed decay. By dry biomass reduction, all factors had statistically very significant impact both as individual and in mutual interaction, on the resaults except on Bilderdykia convolvulus where nozzle impact was not statistically signifiacant.
Keywords: Nicosulfuron, Efficacy, Adjuvants, Nozzle, Weeds.